Effect of Convergent Absorber Tube on Performance of Nanofluid Based Parabolic Trough Collector - Babbar, Anuj (My University, 2017)
Solar collector is one of the efficient devices to utilize the solar energy. To trap maximum solar energy, a lot of changes and approximations have been done in conventional solar heat collectors. In which one of the method is by changing working fluid that can absorb maximum solar energy. Nanofluid plays a major role in heat transfer field. In this proposed thesis work, an attempt has been made to enhance the performance of solar collector, by changing the geometry of absorber tube. An experimental investigation is done on parabolic trough collector, having a convergent absorber tube and making use of nanofluid as working fluid. Experiments were conducted in convergent and straight absorber tube (inlet diameter is 31 mm and outlet diameter is 12.7 mm). Two different working fluids were used, distilled water andAl2O3-H2O nanofluid of different volumetric concentration 0.01%, 0.045% and 0.08% of, at 150LPH, 200LPH, and 250LPH mass flow rates. To investigate the performance of solar heat collector, heat gain by working fluid, instantaneous efficiency, and thermal efficiency were evaluated. It was observed that instantaneous efficiency of convergent absorber tube is slightly more (5% to 10%) than that of straight absorber tube for Al2O3–H2O nanofluids of 0.01% and 0.045% volumetric concentration at 150LPH and 200LPH mass flow rates. It was also observed that with increase in mass flow rate instantaneous efficiency increases from 65% to 78%, as mass flow rate increases from 150 LPH to 250 LPH. Some of the thermophysical properties such as; thermal conductivity, viscosity, density, and pH were also analyzed, as they play important role to determine the efficiency of PTC. It was noticed that ratio of thermal conductivity of Al2O3-H2O nanofluids to the base fluid increases with rise in temperature. Whereas, with time viscosity and density of Al2O3-H2O nanofluids decreases with time i.e. viscosity vary from 5 % to 9 % and density decreases from 3% to 7%.
Master of Engineering -Thermal Engineering
Keywords: Solar energy; convergent absorber tube; thermal conductivity; nanofluid; PTC